Calibration and evaluation of a broad supersaturation scanning (BS2) cloud condensation nuclei counter for rapid measurement of particle hygroscopicity and cloud condensation nuclei (CCN) activity - N. Kim (Copernicus Publications, 2021)
For understanding and assessing aerosol–cloud interactions and their impact on climate, reliable measurement data on aerosol particle hygroscopicity and cloud condensation nuclei (CCN) activity are required. The CCN activity of aerosol particles can be determined by scanning particle size and supersaturation (S) in CCN measurements. Compared to an existing differential mobility analyzer (DMA) with CCN activity measurement, a broad supersaturation scanning CCN (BS2-CCN) system, in which particles are exposed to a range of S simultaneously, can measure the CCN activity with a high time resolution. Based on a monotonic relation between the activation supersaturation of aerosol particles (Saerosol) and the activated fraction (Fact) of the BS2-CCN measurement, we can derive κ, a single hygroscopicity parameter, directly. Here, we describe how the BS2-CCN system can be effectively calibrated and which factors can affect the calibration curve (Fact−Saerosol). For calibration, size-resolved CCN measurements with ammonium sulfate and sodium chloride particles are performed under three different thermal gradient (dT) conditions (dT=6, 8, and 10 K). We point out key processes that can affect the calibration curve and thereby need to be considered as follows: first, the shape of the calibration curve is primarily influenced by Smax, the maximum S in the activation tube. We need to determine appropriate Smax depending on the particle size and κ to be investigated. To minimize the effect of multiply charged particles, a small geometric mean diameter (Dg) and geometric standard deviation (σg) in number size distribution are recommended when generating the calibration aerosols. Last, Fact is affected by particle number concentration and has a decreasing rate of 0.02 per 100 cm−3 due to the water consumption in the activation tube. For evaluating the BS2-CCN system, intercomparison experiments between typical DMA-CCN and BS2-CCN measurements were performed with a laboratory-generated aerosol mixture and ambient aerosols. Good agreement of κ values between DMA-CCN and BS2-CCN measurements for both experiments shows that the BS2-CCN system can measure CCN activity well compared to the existing measurement method and can measure a broad range of hygroscopicity distributions with a high time resolution (∼1 s vs. a few minutes for a standard CCN activity measurement). As the hygroscopicity can be used as a proxy for the chemical composition, our method can also serve as a complementary approach for fast and size-resolved detection and estimation of aerosol chemical composition.